Evaluation of No Alcohol in the Auspicious Year Campaign of Main Service Contractor, Khlong Luang Hospital, Pathum Thani 2007 - Sungprasit, Chavalit (Journal of Health Science of Thailand, 2018)
The study objective was to assess the operation performance of no alcohol in the auspicious year campaign and to study the format of community participation in solving the alcohol drinking problem at Khlong Luang, Pathum Thani Province. The research samples included 35 leaders from 7 communities and 7 government agencies from public health centers chosen by purposive selection. The study was conducted from January to March 2008. Data were collected in in-depth interview, focus group discussion and by questionnaire. The quantitative data was statistically described in terms of frequencies, percentage, means, and standard deviations. The qualitative data analysis was based on content analysis applying CIPP model. The study showed that, from environment perspective, community leaders had high level of perception of the clarity of objective, consistency to government policy and suitability to the current problems. From input factor perspective, they had high level of adequacy of financial budget, supportive materials, and operational skill. But small number of operational personnel resulted in low coverage of operational community. From the process perspective, the communication activity was at a high level with the rehearsal and clarification among operation personnel during and after the operation. This resulted in the understanding of objectives and motivation in order to fully participate in the activities. From output perspective, seven villages showed similar operation pattern. Some activities were different according to community context. The overall participation process in the campaign includes the survey of information on drinking members of community in order to identify problems, rating them , planning accordingly and taking drinkers to visit Tanyarak institute. The continuing activities were required with support and assistance from health centers officers. It was concluded that cooperation of community plays an important role in solving the problem of alcohol drinking. Therefore, the campaign should be expanded to other communities in Khlong Luang. Continuous Monitoring and follow up can also strengthen and develop community leadersี competency.